The city in motion - Macaulay Lewis, ER (2007)
This dissertation examines the interaction between leisured movement and space in Rome from 100 BC – AD 150, primarily drawing upon archaeological evidence from Rome, central Italy and the Bay of Naples. This thesis argues that leisured movement was significant and that an examination of the relationship between leisured movement and space provides new insights into Roman architecture, gardens, attitudes to design and space. Chapter one reviews the theoretical models associated with the study of movement and space in various disciplines and utilitizes these approaches to formulate the theoretical basis for this thesis. Previous scholarship on movement and space in the Roman world is also reviewed to demonstrate the need for further study. Chapter two focuses on ancient literature and epigraphy to examine leisured movement in ancient Rome and the spaces identified as locations for leisured movement. In chapter three the Severan marble plan and the archaeological evidence for the monumental porticos and temple-porticos in Rome, the public and urban context for leisured walking, are analyzed. An examination of the relationship between leisured movement and space in high-status Roman villas and residences is undertaken in chapter four. Walking, driving, riding and boating and their spatial context played an important role in these high-status residences. Finally, chapter five examines the relationship between leisured movement and space in Pompeian houses, in order to understand how leisured movement functioned in such houses and to demonstrate that leisured movement also had a role in the lives of those below the top of Roman society. This thesis demonstrates that movement was a prominent leisure activity and that it was a complex way through which the Romans negotiated Greek culture. It also establishes that Rome’s public porticos and portico-temples, which housed leisured movement, were original contributions to the architectural canon. Movement and space were interconnected phenomena that interacted upon each other; the design of private and public gardens and porticos often created an ordered approach to movement and space. In sum, leisured movement is a productive lens through which we can study Rome, her cultural and leisure activities, approach to design and conception of space.